Applied Human Anatomy - Nolan, Michael F; McNamara, John P (Open textbook library., 2022)
The structure of the human body is usually considered in courses in gross anatomy. These courses typically consist of lectures by the faculty, readings in assigned textbooks and the study of photographs and illustrations in human anatomy atlases. However, as student’s progress through the curriculum and move into the more clinical or practice oriented phases, many discover that the anatomical knowledge they actually need is somewhat different from the kind they possess. What many encounter is difficulty in applying their knowledge to a clinical setting. Applied Human Anatomy was created to better integrate material that is more often than not treated separately in contemporary health care curricula. It is hoped that through this integration students will develop a deeper and more lasting knowledge and understanding of human anatomy as they are likely to need it in the evaluation and management of patients.